Relationship between learning styles and effectiveness of online learning systems. (24th January 2013) - Gu, Vicky Ching; Triche, Jason; Thompson, Mark A.; Cao, Qing
Online learning has become a popular medium to disseminate knowledge for both institutions of learning and for companies. The economic benefits to deliver knowledge and training online are well documented; however, there are still issues as to its effectiveness. One way that online learning may be more effective is by taking into account a student's learning style. Our research seeks to understand if online learning tools account for learning styles, will users find them useful and easier to use thus resulting in a successful online learning environment? We propose an extended Technology Acceptance Model (TAM) to include learning styles as an external variable. Our results show significance for six of the seven hypotheses. Educators and corporate training departments can use these findings to design a better online learning environment for their students and workforce.